2017
DOI: 10.1186/s13002-017-0139-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functionality of the few: current and past uses of wild plants for food and healing in Liubań region, Belarus

Abstract: BackgroundThis study examined the use of wild plants in the food, medicinal and veterinary areas within a small territory limited to one village council in the Liubań district of Belarus. The objectives of the research were to document the current and past uses of wild plants in this region for food and human/animal medication; to analyse the food, medicinal and veterinary areas in the context of wild plants; and to qualitatively compare the results with relevant publications concerning the wild food plants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 26 publications
2
58
0
5
Order By: Relevance
“…Similarly, we recorded only 35 taxa used among Boikos (Pieroni and Sõukand 2017) and 40 taxa among Hutsuls (Sõkand and Pieroni 2016). It is also higher than the number of taxa recorded in areas neighboring Ukraine: 44 taxa used by Ukrainians in Maramures (Łuczaj et al 2015) and 58 taxa used in central Belarus (Sõukand et al 2017). Yet it is important to note that a large number of the taxa (30) are used only in the Chernihiv region, whereas the number of taxa used solely in the Ljubeciv region is clearly comparable with neighboring regions.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Similarly, we recorded only 35 taxa used among Boikos (Pieroni and Sõukand 2017) and 40 taxa among Hutsuls (Sõkand and Pieroni 2016). It is also higher than the number of taxa recorded in areas neighboring Ukraine: 44 taxa used by Ukrainians in Maramures (Łuczaj et al 2015) and 58 taxa used in central Belarus (Sõukand et al 2017). Yet it is important to note that a large number of the taxa (30) are used only in the Chernihiv region, whereas the number of taxa used solely in the Ljubeciv region is clearly comparable with neighboring regions.…”
Section: Discussionmentioning
confidence: 81%
“…changes to state borders, Sõukand and Pieroni 2016), ethnicity (Pieroni and Quave 2005), religion (Bellia and Pieroni 2016;Pieroni et al 2011), socioeconomic conditions (Stryamets et al 2015) and remoteness (Bussmann et al 2016) were found to have a strong influence on the use of wild food plants. The use of wild food plants, compared with the use of medicinal plants, is more homogenously distributed within a population (Sõukand et al 2017) and more evenly shared by different ethnic groups inhabiting the same ecological niche (Quave and Pieroni 2015) or the same ethnos divided by a state border (Sõukand and Pieroni 2016). Uses of wild food plants are mainly learned during childhood and nowadays are often subject to abandonment rather than valorization (Kalle and Sõukand 2016;Reyes-García et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These were mainly the unpublished questionnaires of Józef Rostafiński from 1883, as well as a handwritten monograph of Michał Fedorowski from the same period [16], as well as contemporary field work data by some of the co-authors of the paper. The contemporary studies dedicated to wild plants used as food, medicine and for animal wellbeing were performed recently in Liubań district, Minsk region by Sǒukand and collegues [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Though undomesticated, the harvesting of wild grass seeds has occurred on all inhabited continents [37], and persists right up to the present day in many parts of the world, even though seed collection and processing can be challenging for various reasons such as widespread distribution paterns with low abundance, shatering, lodging or competition with more dominant species. People turn to gathering wild grass seeds for various reasons-as a basic survival strategy to counter famine, poverty or economic depression, to maintaining traditional agricultural practices, preserving the traditional recreational or cultural activities of gathering of local wild food and plant medicines [29,[38][39][40], or for ecosystem restoration and biodiversity conservation purposes [41][42][43].…”
Section: Historical Perspective On Poaceae As Foodmentioning
confidence: 99%